2006
DOI: 10.1016/j.jcta.2005.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Colouring lines in projective space

Abstract: Let V be a vector space of dimension v over a field of order q. The q-Kneser graph has the kdimensional subspaces of V as its vertices, where two subspaces and are adjacent if and only if ∩ is the zero subspace. This paper is motivated by the problem of determining the chromatic numbers of these graphs. This problem is trivial when k = 1 (and the graphs are complete) or when v < 2k (and the graphs are empty). We establish some basic theory in the general case. Then specializing to the case k = 2, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Two vertices of qK n:k are adjacent if and only if the corresponding k-subspaces are disjoint. In [3], the chromatic number of the q-Kneser graph qK n:2 is determined, and the minimum colorings are characterized. In [18], the chromatic number of the q-Kneser graph is determined in general for q > q k .…”
Section: The Electronic Journal Of Combinatorics 17 (2010) #R71mentioning
confidence: 99%
See 1 more Smart Citation
“…Two vertices of qK n:k are adjacent if and only if the corresponding k-subspaces are disjoint. In [3], the chromatic number of the q-Kneser graph qK n:2 is determined, and the minimum colorings are characterized. In [18], the chromatic number of the q-Kneser graph is determined in general for q > q k .…”
Section: The Electronic Journal Of Combinatorics 17 (2010) #R71mentioning
confidence: 99%
“…It remains to settle the case n = 7, k = l = 3, and q 3. By Lemma 2.4, we can choose a 1-space E such that |F E | |F |/ 3 1 and a 2-space S on E such that |F…”
Section: The Case L = Kmentioning
confidence: 99%
“…For k = 2, the chromatic number was determined earlier by Chowdhury et al [14]. For that case they proved χ(qK n:k ) = n−1 1…”
Section: Moreover Equality Holds If and Only If F = {F ∈ V Kmentioning
confidence: 82%
“…If L(x i ) is the set of lines incident with x i , it follows that the sets L(x i ) provide a covering of the Kneser graph of lines by independent sets. These Kneser graphs have been studied in [5] where it was shown that also they have chromatic number q 2 + q. Clearly every coloring of the Kneser graph of lines of PG(3, q) provides a coloring of the graph of chambers studied in the present paper, by replacing each color class C by the set of all chambers whose line lies in C. Therefore the optimal colorings in both graphs correspond to one another and therefore we refer to [5] for further information.…”
Section: A Stability Resultsmentioning
confidence: 99%